Architecture build and design building through virtual reality / Muhammad Faris Mohd Sharidan and Siti Nuramalina Johari - Mohd Sharidan, Muhammad Faris; Johari, Siti Nuramalina (College of Computing, Informatics, and Mathematics, 2024)
Virtual reality (VR) is a cutting-edge tool for exploring the creative field of architecture, transforming the way structures are designed and constructed. This abstract investigates the relationship between technology and architecture, emphasising how virtual reality has a transformative impact on the building process. The building process is hampered by a lack of communicating visualisation ideas in building design and a lack of medium in the planning phase. modes of communication Virtual reality improves spatial comprehension and design precision by enabling dynamic collaboration between architects and stakeholders from concept to immersive simulations. The process will follow an agile methodology. This concise examination of the combination of imagination and technology will redefine the future of building design and construction processes, ushering in a new era in which virtual environments serve as the canvas for architectural brilliance.